Computation-guided design of a laccase-COOH-SWCNT/SPCE electrochemical biosensor for selective tyramine detection - Mas'od, Nurul Hana; Abdul Bahari, Mohammad Nazri; Azhari, Syaza; Mohamad Jamali, Mohamad Arif; Misral, Nadrahtul Huda; Amir Hamzah, Amir Syahir (Elsevier, 2026)
Tyramine (TYM) is a key spoilage biomarker in meat products, creating a need for rapid and selective on-site detection technologies. This study presents a computation-guided strategy integrating molecular docking, molecular dynamics (MD), and molecular mechanics Poisson–Boltzmann surface area (MM/PBSA) free-energy analysis with experimental biosensor fabrication to rationalize and enhance TYM recognition by laccase (LAC). Docking and MD simulations revealed that TYM binds within a hydrophobic pocket near the T1 copper site, anchored by a hydrogen bond with Ala80 and stabilized by Phe344, Pro346, Leu112, and Leu459. The LAC–TYM complex remained structurally stable over 100 ns, and MM/PBSA yielded a favorable binding free energy (ΔG_bind ≈ −22.6 kcal/mol), predominantly driven by van der Waals interactions. Guided by these atomistic insights, a LAC–COOH-SWCNT/SPCE biosensor was constructed and characterized by field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM), confirming uniform enzyme immobilization. Differential pulse voltammetry (DPV) exhibited a linear range of 2.58 × 10−5 to 1.92 × 10−4 M with a limit of detection (LOD) of 7.75 × 10−6 M, a limit of quantification (LOQ) of 2.58 × 10−6 M, a sensitivity of 0.0136 μA mM−1 and exhibited a high correlation coefficient (R2 = 0.984). The sensor demonstrated strong selectivity, minimal interference from structurally unrelated biogenic amines, and good recoveries (78.2–105.8%) in spiked chicken meat samples. This work establishes a unified computation-to-experiment framework for biosensor engineering and highlights the potential of atomistic modelling to guide enzyme–nanomaterial interface design for food safety applications.